Application of the Theory of Planned Behaviour to Predict College Students’ Online Purchase Intention : A Systematic Review and Meta-Analysis - Linge, Ashish; Singh, Mahesh; Kakde, Baldeo; Punjani, Krunal K. (Indian Journal of Marketing, 2022)
The main aim of this study was to review and synthesize the literature on the theory of planned behavior (TPB) tested empirically by researchers worldwide to predict college students’ online purchase intention using its antecedents. This article meta-analyzed the correlations between the three independent constructs of TPB: attitude, subjective norms, perceived behavioral control, and one dependent construct, purchase intention. The researchers reviewed 1,798 articles generated through seven electronic database searches for the period from 2003 – 2020. These studies were screened against the inclusion-exclusion criteria using PRISMA, leaving 15 study records for performing a systematic review and meta-analysis. The findings confirmed a strong relationship between attitude and purchase intention, subjective norms and purchase intention, and perceived behavioral control and purchase intention. This indicated that the TPB constructs significantly predicted the online purchase intention of college students.